Design of Alternative Energy Using Thermoelectricity by Utilizing a Dispenser Heat Tank Using IOT - Legenda Prameswono, Pratama; Sinka, Wilyanti; Adi, Setiawan; Hamzah, Hamzah; Mauludi, Manfaluthy; Yanuar Zulardiansyah, Arief; Safaa Najah Saud, Al-Humairi (Politeknik Negeri Semarang, 2024)
Energy is an object that can move through essential reactions; increasing population growth is one of the factors for increasing energy needs. One of the initiatives initiated was the creation of a Thermal Electric Generator (TEG). The formulation of the problem in this study is to determine the output voltage, current, and power generated by the thermoelectric as an alternative energy and to determine the effect of temperature on the thermoelectric. The goal is to determine the amount of output the thermoelectric generates when it gets a heat source from the dispenser. The data source in this study was obtained from testing the tools made. The test results show the effect of temperature on the thermoelectric tested for 120th minutes test of max 5.96 Volts with a water temperature in the dispenser tank of 73oC without using a step up using six pieces of thermoelectric arranged in series.